PENERAPAN METODE JALUR KRITIS ATAU CRITICAL PATH METHOD (CPM) PENENTUAN WAKTU OPTIMAL DALAM PROSES PEMBUATAN KERAJINAN TENUN IKAT TRADISIONAL KUPANG NTT (Jurnal Ilmiah Soulmath : Jurnal Edukasi Pendidikan Matematika, 2016)
East Nusa Tenggara Province is known to have many traditional woven craft, one that is well known by the public is Kupang Ikat woven. Enterprises weaving is still managed traditionally built with familial management and expertise only found in hereditary. In addition, to determine the timing of production of Kupang ikat woven still using forecasting as a guide. The forecasting results in the absence of standard production time. One method that can be used for determining the optimal time is the critical path method (CPM). This method is part of a network methods oriented work on determining the time schedule and estimate deterministic (certain). Research shows that the production time ikat Kupang woven is 20 days.Keyword : CPM, network, ikat Kupang woven